2017
DOI: 10.1016/s1473-3099(16)30319-x
|View full text |Cite
|
Sign up to set email alerts
|

Import and spread of extended-spectrum β-lactamase-producing Enterobacteriaceae by international travellers (COMBAT study): a prospective, multicentre cohort study

Abstract: Netherlands Organisation for Health Research and Development (ZonMw).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

40
457
6
10

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 394 publications
(513 citation statements)
references
References 29 publications
40
457
6
10
Order By: Relevance
“…In that study, the strongest predictors for acquisition of ESBL-producing E. coli were geographic destination (notably South Asia), antibiotic use during travel, traveller's diarrhea and pre-existing chronic bowel disease. 18 Eating at street food stalls, consumption of raw vegetables, contact with orphan children, staying in a hostel or guest house, visiting local markets and staying in rural areas were additional strong predictors of colonization with ESBL-producing E. coli.…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…In that study, the strongest predictors for acquisition of ESBL-producing E. coli were geographic destination (notably South Asia), antibiotic use during travel, traveller's diarrhea and pre-existing chronic bowel disease. 18 Eating at street food stalls, consumption of raw vegetables, contact with orphan children, staying in a hostel or guest house, visiting local markets and staying in rural areas were additional strong predictors of colonization with ESBL-producing E. coli.…”
Section: Discussionmentioning
confidence: 97%
“…17 The largest and most comprehensive travel study investigating multidrug-resistant E. coli colonization among returning travellers was performed in the Netherlands. 18 The authors studied more than 1800 travellers who were negative for ESBL-producing E. coli before travel; of Enrolled in study n = 149 (71%)…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A prospective study from 2017 [36] showed that up to 75% of the investigated travelers returning from, e. g., India, had acquired Enterobacteriaceae, which produce broad-spectrum β-lactamases. Although these tourists are primarily symptom-free carriers of MDR pathogens, these bacteria could become relevant in the case of an infection (e. g., abdominal infection).…”
Section: Epidemiologymentioning
confidence: 99%
“…Acquisition rates of ESBL-PE by European travelers are about 30% in America, 40% in Africa, and 70% in Asia [4]. ESBL-PE acquisition after travel is able to diffuse to other family members in 12% of the cases [5]. ESBL-PE carriage in healthy people is 14% worldwide on average and increases by more than 5% per year [6].…”
Section: Emergence Of Resistant Bacteria Worldwide: a Need For Antibimentioning
confidence: 99%